"Cold and wet" and "warm and dry" climate transitions at the East Asian summer monsoon boundary during the last deglaciation. (1st November 2022) - Yue, Jiaojiao; Xiao, Jule; Wang, Xu; Meckler, Anna Nele; Modestou, Sevasti Eleni; Fan, Jiawei
Abstract: Studies on millennial‒centennial abrupt climate events during the last deglaciation have significant relevance to modern-day abrupt and extreme climate changes that are occurring more frequently in the context of global warming. The northwestern margin of the modern East Asian summer monsoon (EASM) region is particularly sensitive to such climatic changes. In this study, we employed the continuous sedimentary core sequence of Dali Lake, located on the north-western edge of the EASM region. Carbonate clumped isotope (Δ47 ) thermometry was applied to both fine-grained endogenic carbonates and ostracod ( Limnocythere inopinata [Baird]) shells in the lake core sediments to quantitatively reconstruct lake water temperature and oxygen isotope (δ 18 OW [VSMOW]) changes during the period from approximately 15.6–10.5 cal kyr BP (calibrated years before the present; abbreviated to "kyr"). Fine-grained endogenic carbonate Δ47 temperatures suggest that the lake surface water temperature changes may have been mainly controlled by the northern high latitudes, reflected in the corresponding millennial‒centennial abrupt climate events (such as a 5–6 °C decrease of summer surface water temperature during approximately 12.9–11.8 kyr, indicative of Younger Dryas [YD] cooling). Ostracod shell Δ47 temperatures complement the endogenic carbonates but appear to be affected by changes in calcification season, likely linked to climatic changes. These data suggest a climatic shift at approximately 15.2 kyr, before the onset of the Bølling‒Allerød (BA) interstadial, which is interpreted as general warming. δ 18 OW from the endogenic carbonates is interpreted as changes in precipitation and conforms well with 18 O isotope changes in Greenland ice cores, suggesting that the precipitation changes may have been influenced by the northern high latitudes. Regional rainfall increased during the Heinrich event 1 (H1) and YD stadials, whereas it appears to have decreased in the BA and during the early Holocene (EH). This study indicates that the primary climate pattern at the northwestern boundary of the EASM region during the last deglaciation was characterized by alterations of "cold and wet" and "warm and dry" climate, rather than the more typical "cold and dry" versus "warm and wet" pattern. Highlights: Millennial‒centennial abrupt climate events. Δ47 thermometry was applied to both fine-grained endogenic carbonates and ostracod shells from the Dali Lake core. The main climate pattern of Northern China during the last deglaciation was "cold and wet" and "warm and dry".